Unusual mimicry: Pancreatic hematoma masquerading as laceration in abdominal trauma imaging - M. Karthick Sriram; Paul Yohan George; Prakash Joseph; Kirthi Sathyakumar; Vijayan Purushothaman (Journal of Current Research in Scientific Medicine)
Abdominal trauma often presents with complex challenges, especially when multiple organs are involved. We report a case of a 20-year-old male involved in a road traffic accident with handlebar injury to the abdomen. Initial imaging suggested hollow viscus perforation, Grade II liver injury, Grade IV spleen, and Grade III pancreatic injury (full-thickness pancreatic laceration). Emergency laparotomy revealed bleeding spleen, liver laceration, and duodenal and gastric perforations, but no evidence of pancreatic laceration upon exploration. He underwent splenectomy and repair of gastric and duodenal perforations. As the pancreas was normal, pancreatectomy was deferred. Postoperatively, the patient’s condition deteriorated, prompting relook surgery 48 h later, revealing an intact pancreas with ischemia of the body and tail. This is probably attributed to compression by an intraparenchymal hematoma. Distal pancreatectomy was performed, resulting in the patient’s recovery. This is the first case being reported where an intraparenchymal hematoma has mimicked a full-thickness laceration of the pancreas. There are no other reported cases in the literature of a pancreatic hematoma mimicking a laceration on cross-sectional imaging.